Analysis Of The Incidence Of Teaching English In Students Of Second Year Of High School At Unidad Educativa “San Vicente De Paul” Riobamba City, Chimborazo Province In The Academic Year 20216-2017. - Martínez Chávez, Alfonso Fabian (2017)
The low competence in English language learning in students of second year of high school at Unidad Educativa "San Vicente de Paul" in Riobamba city, Chimborazo province in the academic year 20216-2017. In this research will use the scientific method because through this, it is possible to get the appropriate data to understand, analyze and interpret the factors that incidence in the teaching English with students of second year of high school. This research project is based on the analysis of the influence of the teaching of English to student, this general research objective is to evaluate the incidence of teaching English to students of second year, explore through observation because we defined the problem, it was applied to 17 students and 3 teachers, of English area, the benefits that has for students the learning and the ability to speak a second language, which is very powerful for their future, it took place in the academic period, September 2016-March 2017, and then propose some solutions, based on those results, some conclusions and recommendations are suggested. This research was carried out in an exploratory way through the ethnographic method which helped to describe analyze, explore, and clarify the ideas of the problem mentioned. Results which allow to formulate a strategy that will be able to find a way to solve the founded problem.